Analisis Bentuk Perkembangan Wilayah Kecamatan Kartasura Sebagai Kawasan Strategis Cepat Tumbuh - Anisah Anisah; Soedwiwahjono Soedwiwahjono; Nur Miladan (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2017)
Regional development based on spatial will form a pattern due to the character that develop in it. The pattern can be formed by the network, hierarchy, and so forth. The influence of policies that encourage development to bring new activities in the region is also capable of bringing changes. As a rapidly growth strategic area established by the district government, Kartasura District has variety of new activities. This research is used to know how the development on regional form of Kartasura District as a rapidly growth strategic area. It uses longitudinal development method with analytical approach used is deductive and quantitative descriptive research type. The compilation and analysis techniques used are primary data collection (observation) also secondary; Descriptive statistics, GIS and overlay, breaking point. The result of this research are the development of Kartasura sub-district as rapidly growth strategic area which is formed pattern based on the network also the limitation of development as a result of supporting policy causing the difference internal development on Kartasura District.